Scientific Research Activities of the Republican Institute of Russian Language and Literature Pedagogy (1964–1990) - Ramazanov , Ulugbek (The Lingua Spectrum, 2026)
This article provides a comprehensive analysis of the research works, the system of training scientific and pedagogical staff, and the activities of scientific publications carried out in the second half of the 20th century at the Republican Pedagogical Institute of Russian Language and Literature, based on historical sources. The study thoroughly describes the establishment of the institute, the stages of development of its scientific and pedagogical potential, the composition of the faculty, and their academic activities. It also deeply examines the postgraduate system, dissertation defenses, the formation of scientific schools, and the dynamics of the development of scientific personnel training. The article consistently analyzes the system of organizing research activities at the institute and its stages of development based on state-level decisions, decrees, and regulatory legal documents. It substantiates the effective implementation of textbooks, teaching manuals, and methodological materials created by the institute’s scholars into the educational process. The results of the study show that the institute has become a leading scientific center in the fields of Russian language teaching methodology, linguistics, and literary studies, and has made a significant contribution to the development of the national education system. In addition, the contribution of the research work conducted at the Institute of Russian Language and Literature to the development of republican scientific research is separately studied and examined in detail.